The study on star fruit extract as bleaching agent for treating yellowed cotton textile - Barkeshli, Mandana; Abd Rahim, Aishah (2013)
In Asia the tradition of using natural products for preservation and conservation of art works has been common along the history and still in practice. Malaysia being rich in natural resources the tradition of using local herbs, fruits and plants has been common among the craftsmen to preserve their cultural heritage. In this paper as the case study the extract of star fruit that has been used historically as stain removal on cloth in Malaysia, were selected and studied. The present study is aimed to study scientifically this alternative natural material for textile bleaching of yellowed cotton textile using star fruit extract. In this research a scientific laboratory work was carried out to investigate the effectiveness of this traditional technique of stain removal by using color Spectrophotometer analysis. Our research showed that star fruit extract is effective on cotton textile. It can be considered as green conservation practice and can be applied on cotton cloth as an alternative bleaching agent and stain removal which is sustainable and eco-friendly product.